Immunofluorescence microscopy of healthy skin from patients with systemic lupus erythematosus: more than just the lupus band. - Velthuis, P J (1992)
Many papers have been published on the lupus band in systemic lupus erythematosus (SLE), but little information exists on the possible diagnostic value of the lupus band and other microscopic immunofluorescence phenomena found in clinically normal skin of patients with SLE. In a study of 297 subjects (66 patients with SLE, 81 patients with other forms of LE, and 150 patients with other systemic connective tissue disorders) it was found that: (a) granular deposits of IgA, IgG, and IgM in the basal membrane zone and in the deeper blood vessels were more common in patients with SLE than in the other two groups; (b) depending on the clinical differential diagnosis, IgA and IgG deposits at the epidermal basal membrane can be specific for SLE; (c) using logistic regression analysis sets of variables can be selected with a high potential to discriminate between SLE and the other groups; and (d) immunofluorescence variables do not duplicate the information for the diagnosis of SLE given by the American Rheumatism Association (ARA) criteria or other laboratory methods. From these results, it is concluded that immunofluorescence microscopy of clinically normal skin is a valuable diagnostic method which should be reconsidered as a potential criterion for the diagnosis of SLE in the next evaluation of the ARA criteria.